MO503SAFETY AND EFFICACY OF ANTICOAGULATION IN PATIENTS WITH EGFR<30 ML/MIN/1.73 M2 AND ATRIAL FIBRILLATION. (29th May 2021) - Freese Ballegaard, Ellen Linnea; Bjerring Olesen, Jonas; Kamper, Anne Lise; Feldt-Rasmussen, Bo; Gislason, Gunnar; Torp-Pedersen, Christian; Carlson, Nicholas
Abstract: Background and Aims: Net benefit of anticoagulation in patients with eGFR <30 ml/min/1.73 m2 and atrial fibrillation remains uncertain. The aim of this study was to evaluate the use, efficacy and safety of anticoagulation therapy in patients with eGFR<30 ml/min/1.73m 2 (including dialysis treated patients) and atrial fibrillation. Method: In a retrospective cohort study, all patients with atrial fibrillation and eGFR<30 ml/min/1.73 m 2 were identified in nationwide Danish registers between 2008 and 2018. Cumulative incidences of stroke and major bleeding stratified on anticoagulation treatment were computed using the Aalen-Johansen estimator. One-year risks of stroke and major bleeding were calculated with comparison of treatment vs. no treatment based on Cox regression models adjusted for age, sex and dialysis status with G-computation of one-year risks standardized to the distribution of risk factors in the sample. Major bleeding was defined as any diagnosis of bleeding leading to hospitalization. Results: A total of 2, 452 patients with eGFR <30 ml/min/1.73 m 2 and de novo atrial fibrillation were identified. Mean age was 78.8 years, 51.3% were male and 20% received dialysis therapy. Anticoagulation therapy was initiated in 877 patients (35.8%), with warfarin accounting for 58.6% of all prescriptions. Overall, one-year standardized risk of bleeding was 10.6% (95% confidence interval (CI) 8.7%-12.7%) and 8.2% (95% CI 6.9%-9.5%) in patients with and without anticoagulation, while the risks of stroke were 3.6% (95% CI 2.6%-4.5%) and 5.1% (95% CI 4.1%-6.1%), respectively. In subgroup analyses of patients dependent vs. non-dependent on dialysis, the standardized one-year risk of bleeding was 13.3% (95% CI 9.0%-19.8%) vs. 10.4% (95% CI 8.6%-12.4%) in patients with anticoagulation and 9.0% (95% CI 6.5%-12.0%) vs. 7.8% (95% CI 6.5%-9.2%) in patients without anticoagulation. While the risk of stroke was 3.5% (95% CI 0.8%-6.7%) vs. 3.5% (95% CI 2.5%-4.9%) in patients with anticoagulation and 5.7% (95% CI 3.5%-7.8%) vs. 4.9% (95% CI 3.7% vs. 6.3%) in patients without anticoagulation. Cumulative incidences of major bleeding and stroke are shown in the figure. Conclusion: Use of anticoagulation was associated with increased risk of bleeding and reduced risk of stroke in patients with eGFR<30 ml/min/1.73 m 2 and atrial fibrillation. Randomized controlled trials are needed to establish the benefit and harm of anticoagulation in this population.